2000
DOI: 10.1590/s0100-879x2000001100003
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the expression of native Mycobacterium tuberculosis phospholipase C: recognition by immune sera and detection of promoter activity

Abstract: The genome of Mycobacterium tuberculosis H37Rv contains three contiguous genes (plc-a, plc-b and plc-c) which are similar to the Pseudomonas aeruginosa phospholipase C (PLC) genes. Expression of mycobacterial PLC-a and PLC-b in E. coli and M. smegmatis has been reported, whereas expression of the native proteins in M. tuberculosis H37Rv has not been demonstrated. The objective of the present study was to demonstrate that native PLC-a is expressed in M. tuberculosis H37Rv. Sera from mice immunized with recombin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Moreover, sphingomyelinase and phospholipase C activities were detected in cell extracts from M. tuberculosis and in Mycobacterium smegmatis overexpressing recombinant PlcA or PlcB (Johansen et al, 1996). The product of the plcA gene was detected in cell extracts from M. tuberculosis grown in vitro and inside macrophages (Matsui et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, sphingomyelinase and phospholipase C activities were detected in cell extracts from M. tuberculosis and in Mycobacterium smegmatis overexpressing recombinant PlcA or PlcB (Johansen et al, 1996). The product of the plcA gene was detected in cell extracts from M. tuberculosis grown in vitro and inside macrophages (Matsui et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The role of phospholipase in intracellular survival and as a virulence factor has been demonstrated in bacterial species such as Listeria monocytogenes [48]. M. tuberculosis genome carries three adjacently located phospholipase C (PLC) genes (plcA, plcB and plcC) that are similar to the P. aeruginosa plc genes and a fourth truncated gene (plcD), separated from this cluster [49]. Bakala N'goma et al [5] were able to obtain high yields of all four pure recombinant M. tuberculosis PLCs and demonstrated that all four enzymes are cytotoxic to mouse macrophages owing to their hydrolytic activity on cell membrane phospholipids.…”
Section: Phospholipase Cmentioning
confidence: 99%
“…PlcA (512 aa) is a membrane-associated phospholipase C1 that was originally identified by mass spectrometry of MTB H37Rv 16 and is encoded by Rv2351c; the expression of the native plcA has been demonstrated through immunoblotting of MTB. 17 PlcA is essential in the pathogenic MTB complex and is found in both MTB and M. africanum , but is absent in all the BCG strains. 18 Because plcA is an antigen located in RD7 of MTB, we evaluated its potential in the diagnosis of TB infection and the development of TB vaccine.…”
Section: Introductionmentioning
confidence: 99%